Model Pembelajaran Matematika Siswa Kelas Satu Sekolah Dasar - Frengky, - (Jurnal Psikologi, 2008)
Optimizing school quality depends on the comprehension to teachingâ€learning processes in the classroom as well as outside classroom. Quality school shows high capacity in optimizing studentsâ€™ ability in certain courses such as in mathematics. The teachingâ€learning processes of Mathematics, wellâ€known as a difficult course among students, needs more attention. This study focused on the observation of the teachingÂ learning processes in Mathematics among first grade students of yunior highâ€school. The study used a qualitative approach with a grounded theory. Participants were recruited from a yunior highâ€school in Yogyakarta. The results showed that students were interested in studying mathematics and consistent guidances were needed in teaching mathematics for students.